Quintus Smyrnaeus' Posthomerica : engaging Homer in late antiquity - Maciver, Calum Alasdair. (Mnemosyne, Supplements, 2012)
Quintus Smyrnaeus' Posthomerica (3rd century C.E.), the 14 book Greek epic on the Trojan War, is a text which has traditionally been overlooked in the main canon of Classical authors, and in fact until only recently has been largely ignored as a literary work. This book, the first monograph in English on the poem since 1904, examines the Posthomerica's close relationship with the Homeric epics, with a focus on the originality and Late Antique interpretative bias of Quintus in his readings and emulation of Homer. The study deals specifically with three separate aspects of poetics, and their Homeric intertextuality: ecphrasis, gnomai, and similes, and their role within the poem's narrative strategies, themes, and aims.